Activity and substrate use of Bothrops atrox (Serpentes: Viperidae) in a floodplain forest in the western Brazilian Amazon - Lima da Fonseca, Wirven (2025)
Basic information on the natural history of species is essential for studies of evolutionary biology and ecology, in addition to being fundamental for developing conservation strategies. This study aimed to provide information on the activity and substrate use of Bothrops atrox in a floodplain forest in the western Brazilian Amazon. With a sampling effort of 816 personhours of time constrained, nocturnal visual search, 28 observations of 27 individuals were made, of which 16 were adults and 11 were juveniles. The encounter rate of B. atrox was one snake every 30 person-hours of searching, and most individuals were recorded during the rainy season. Considering the snake assemblage, Bothrops atrox represented 20.8% of the sampledsnakes, out of a total of 130 individuals of 21 species, being the second most frequent species. The ecological and morphological differences between the congeneric species B. atrox and B. bilineatus in this floodplain forest, as well as resource availability, likely influence their local abundance. These factors would also help minimize the probability of interspecific competition between these syntopic species.